2016
DOI: 10.3389/fcomm.2016.00009
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Semantic Similarity between Metaphor Terms of Visual vs. Linguistic Metaphors through Flickr Tag Distributions

Abstract: This study aims at modeling the semantic similarity between metaphor terms by means of a distributional method based on a Big Data stream: Flickr tags. As explained in the article, this distributional model, Flickr Distributional Tagspace (FDT), captures primarily relational similarity between concept pairs, that is, between tags that appear in similar tagsets (and therefore in similar pictures). A long established view in metaphor theory claims that metaphors pertain to the conceptual dimension of meaning, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…To study the neurocognitive mechanism of pictorial metaphors, different methods have been attempted, such as eye tracking (Indurkhya and Ojha, 2013), EEG (Ma et al, 2016), fMRI (Ojha et al, 2017) and distributional method of semantics (Bolognesi, 2016). Comparatively, ERP is advantageous in terms of high time-resolution and its application to explore the temporal course and dynamic mechanism of pictorial metaphor (Kutas and Hillyard, 1980; Hillyard and Kutas, 1983), which is of great significance to the study of advertising visual stimuli, as the typical observation time for print advertising is two seconds in an editorial context (Pieters et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…To study the neurocognitive mechanism of pictorial metaphors, different methods have been attempted, such as eye tracking (Indurkhya and Ojha, 2013), EEG (Ma et al, 2016), fMRI (Ojha et al, 2017) and distributional method of semantics (Bolognesi, 2016). Comparatively, ERP is advantageous in terms of high time-resolution and its application to explore the temporal course and dynamic mechanism of pictorial metaphor (Kutas and Hillyard, 1980; Hillyard and Kutas, 1983), which is of great significance to the study of advertising visual stimuli, as the typical observation time for print advertising is two seconds in an editorial context (Pieters et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the use of Flickr in our field of research is not new. For example, Bolognesi (2014), by using a distributional approach, built up a semantic space based on Flickr tag co-occurrences (i.e., Flickr Distributional Space, see also Bolognesi, 2016Bolognesi, , 2017 and showed that an inherently visual domain -such as the domain of colour -is better mapped by the Flickr Distributional Space rather than distributional spaces based on solely textual information (Baroni & Lenci, 2010;Landauer & Dumais, 1997). Moreover, Flickr is a gold mine in computer vision research: with its huge numbers of tagged images, it serves as an excellent resource for training convolutional neural networks (e.g., T. Chen et al, 2014;X.…”
Section: What Is Flickr?mentioning
confidence: 99%
“…Furthermore, another type of approach has been proposed which utilizes visual information without directly computing visual vectors from images. Bolognesi's (2016Bolognesi's ( , 2017) Flickr R Distributional Tagspace uses the co-occurrence statistics between user-generated tags that appear in the same image to generate word vectors. In this paper, we use multimodal distributional semantics to model the hybrid view of conceptual representation.…”
Section: Multimodal Distributional Semanticsmentioning
confidence: 99%